Postoperative improvement in DASH score, clinical findings, and nerve conduction velocity in patients with cubital tunnel syndrome - Ido, Yoshikazu (Sci Rep, 2016)
We investigated a recovery pattern in subjective and objective measures among 52 patients with cubital tunnel syndrome after anterior subcutaneous transposition of the ulnar nerve. Disabilities of the Arm, Shoulder and Hand (DASH) score (primary outcome), numbness score, grip and pinch strength, Semmes-Weinstein (SW) score, static 2-point discrimination (2PD) score, and motor conduction velocity (MCV) stage were examined preoperatively and 1, 3, 6, 12, and ≥24 months postoperatively. Statistical analyses were conducted to evaluate how each variable improved after surgery. A linear mixed-effects model was used for continuous variables (DASH score, numbness, grip and pinch strength), and a proportional odds model was used for categorical variables (SW and 2PD tests and MCV stages). DASH score significantly improved by 6 months. Significant recovery in numbness and SW test scores occurred at 1 month. Grip and pinch strength, 2PD test scores, and MCV stage improved by 3 months. DASH scores and numbness recovered regardless of age, sex, or disease severity. It was still unclear if both subjective and objective measures improved beyond 1-year postoperatively. These data are helpful for predicting postoperative recovery patterns and tend to be most important for patients prior to surgery.